S, The Sosialisasi Cek Gula Darah Sewaktu (GDS) dan Pengukuran Tekanan Darah di Desa Pasuluhan Serang - Fitri, Riki Ukhtul; Ade Komariah; Marista Viana; Desty Endrawati Subroto; Rastia Ningsih; Uli Wildan Nuryanto; Syam Ainun Fidiah; Nene Novi Silvia Sa’adah; Naty Masnawati (STIKES Suaka Insan Banjarmasin, 2025)
Diabetes mellitus and hypertension are diseases whose prevalence is alwayshigh in Indonesia. This disease occurs in adults and the elderly. The aim of thisservice is to increase the knowledge of Pasuluan residents regardinghypertension and diabetes mellitus, and whether this disease is not treatedproperly, it will cause ongoing complications. The method applied in thissocialization was to gather all Pasuluan residents to come to the KKM Group05 Command Post to take part in the socialization of spot blood sugar checksand blood pressure measurements. The results obtained from this socializationwere 5 people who had diabetes, 1 person at risk of diabetes, and 19 peoplewere normal, for measuring blood pressure there were 8 people who hadhypertension, 6 people at risk of hypertension, and 11 people normal. It ishoped that they will be able to increase knowledge about diabetes mellitus andhypertension